Analysis of inclinometric observations and prediction of soils deformations in the area of the Dnister PSPP - Zyhar, Andrii; Savchyn, Ihor; Yushchenko, Yuriy; Pasichnyk, Mykola (Національний університет "Львівська політехніка", 2021)
The aim of the research is mathematical analysis and forecasting of dispersive soils behaviour based on the study of inclinometric observations data in the area of the natural-technical system of the Dnister PSPP. Methodology. The research methodology is based on mathematical analysis and modelling of processes occurring in the mountain massif on which the Dnister PSPP is located, using the finite element method. Results. The paper presents an analysis of the results of geotechnical monitoring of the behaviour of dispersive soils, implemented on the basis of inclinometric measurements on the territory of the Dnister PSPP. Quantitative parameters of horizontal displacement distribution in inclinometric wells are established. They made it possible to detect negative dynamics in the geological horizons N1-2ap and N1p+v, which is apparently caused by technogenic load caused by the Dnister upper reservoir. The behaviour of dispersive soils under the influence of natural and technogenic loads has been modelled. Based on the simulation results, the change of the sign of deformations under the influence of additional load, which can be the filling of the Dnister upper reservoir, is confirmed. Obviously, the use of this method alone does not allow full detecting and tracking modern geological, seismic and geodynamic processes. A combination and detailed analysis of different monitoring methods (geophysical, geodetic, parametric, vibrometric, hydrogeological, temperature, visual-instrumental and others), as well as modelling the behaviour of the object under the influence of natural and technogenic factors is optimal. Such simulations could be used in the design of other objects of this type, so this is a promising area for further research. Originality. For the first time, a mathematical analysis and forecasting of the behaviour of dispersed soils in the area of the natural and technical system of the Dnister PSPP was conducted on the basis of studying the data of inclinometric observations. Practical significance. The proposed technique can be used in the design of other objects of this type, as modelling the behaviour of the object under the influence of natural and technogenic factors makes it possible to assess possible risks and prevent them.
Аналіз інклінометричних спостережень та прогнозування деформацій ґрунтів в районі Дністровської ГАЕС
https://doi.org/10.23939/jgd2021.01.017
Keywords: geotechnical monitoring; dispersive soils; stress-strain behaviour; inclinometric wells; Dnister PSPP